Dying in hospital with Parkinson's disease: a retrospective audit. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Samuel, Maria; Ramsell, Amy; Churm, Deepta; Walker, Richard
Abstract : Background: Patients with idiopathic Parkinson's disease (IPD) are most likely to die in hospital or nursing homes. Recognising and managing the end-of-life phase of IPD can be challenging. Complex symptoms such as swallowing difficulties, cognitive problems and hallucinations can be present. Patients may benefit from dopaminergic treatment until the very end, but drug delivery may be difficult. Guidelines have recently been developed to assist clinicians. Aim: To document the prevalence and management of complex symptoms at the end-of-life, and the use of palliative care services and the Liverpool Care Pathway (LCP). Method: This is a retrospective audit of all hospital deaths from 2008 to 2010 of patients with IPD known to the North Tyneside PD service. The last hospital admission during which the patient died was audited from medical records. Results: Medical records were available for 33 out of the 35 patients who fulfilled the criteria of this audit. 58% were male. The average length of hospital stay was 12 days. 21% were documented to have hallucinations, 39% cognitive difficulties and 45% swallowing difficulties. Of those with swallowing difficulties, 13% had an existing percutaneous gastrostomy, 47% had a nasogastric tube and 40% had neither. 27% were started on a Rotigotine patch as dopaminergic therapy. 45% were started on the LCP prior to death. Of those on the LCP, 100% had their dopaminergic therapy stopped at the time of initiating the LCP. 15% were referred to the palliative care team. Conclusion: The recognition of the dying phase in patients with IPD remains difficult. It is recommended that dopaminergic therapy is continued for as long as possible, but swallowing difficulty at the end-of-life is common. The availability of Rotigotine patches may provide a solution to this. Finally, it may be appropriate to continue dopaminergic therapy in some despite initiating the LCP.